Health and GDRP : How Strong is the Influence of Morbidity on Economics? - Almazzaya, Sulthan Razhief; Pratomo, Devanto Shasta (Journal of Development Economic and Social Studies, 2026)
Public health has an important role in supporting regional economic performance, yet the relationship between morbidity and economic output is not always consistent across regions. This study aims to analyze the influence of morbidity on Gross Regional Domestic Product (GRDP) in districts/cities of East Java during 2010–2022, with Government Health Expenditure, Dependency Ratio, and Labor Force Participation Rate (LFPR) as control variables. The study employs a quantitative approach using panel data from 38 districts/cities in East Java. The analysis method used is panel data regression with the Fixed Effect Model (FEM). The results show that morbidity has a positive and significant effect on GRDP, indicating that the relationship between health conditions and regional economic performance is more complex than predicted by human capital theory. Government Health Expenditure and LFPR also have positive and significant effects on GRDP, while the Dependency Ratio has a negative but insignificant effect. These findings imply that regional economic performance is influenced not only by public health conditions, but also by labor market dynamics, fiscal capacity, and regional economic structures, thus requiring more inclusive and adaptive development policies.